Green synthesis of novel magnetic porous organic polymer for magnetic solid phase extraction of neonicotinoids in lemon juice and honey samples. (30th July 2022) - Jiang, Sichang; Meng, Xufeng; Xu, Mingming; Li, Min; Li, Shuofeng; Wang, Qianqian; Liu, Weihua; Hao, Lin; Wang, Junmin; Wang, Chun; Wang, Zhi; Wu, Qiuhua
Highlights: A novel magnetic porous organic polymer (named Rut-MOP) was prepared. The Rut-MOP showed excellent extraction capability to neonicotinoid insecticides. A sensitive method was developed to analyze neonicotinoids in lemon juice and honey. H-bonding, π-π stacking and Lewis acid-base interactions involved in the extraction. Rut-MOP displayed good application prospect for analysis of some other compounds. Abstract: Natural rutin with abundant hydroxyl groups was used as a green monomer to synthesize hydroxyl-functional magnetic porous organic polymer (named Rut-MOP) through environmentally-benign diazo-coupling reaction for the first time. The Rut-MOP displayed high extraction capability for neonicotinoid insecticides (thiamethoxam, imidacloprid, acetamiprid and thiacloprid). Thus, a Rut-MOP based magnetic solid-phase extraction method combined with high performance liquid chromatography was established for sensitive determination of neonicotinoid insecticides in lemon juice and honey samples. Under optimized conditions, the linear response of neonicotinoids was 0.1–100.0 ng mL −1 for lemon juice and 8.0–1000.0 ng g −1 for honey. The limits of detection (S/N = 3) were 0.03–0.04 ng mL −1 and 2.5–3.0 ng g −1 for lemon juice and honey, respectively. The method recoveries were 82–118% with the relative standard deviations of 1.9–7.6%. The results demonstrate that the Rut-MOP based method can be served as a good alternative for the sensitive analysis of neonicotinoid insecticides in lemon juice and honey.